Laminar convective heat transfer of hexylamine-treated MWCNTs-based turbine oil nanofluid. (15th November 2015) - Amiri, Ahmad; Shanbedi, Mehdi; Yarmand, Hooman; Arzani, Hamed Khajeh; Gharehkhani, Samira; Montazer, Elham; Sadri, Rad; Sarsam, Wail; Chew, B.T.; Kazi, S.N.
Graphical abstract: Highlights: A study on CNTs functionalization with hydrophobic group of hexylamine. Rapid microwave-assisted approach employed to reach high yield functionalization. Highly soluble HA-treated MWCNTs in turbine oil were synthesized. Convective heat transfer coefficient of MWCNTs based turbine oil nanofluids investigated. Pressure drop as a negative factor were investigated for various volume concentrations. Abstract: Multi-walled carbon nanotubes (MWCNTs) were functionalized by hexylamine (HA) in a promising, cost-effective, rapid and microwave-assisted approach. In order to decrease defects and remove acid-treatment stage, functionalization of MWCNTs with HA was carried out in the presence of diazonium reaction. Surface functionality groups and morphology of chemically-functionalized MWCNTS were characterized by FTIR, Raman spectroscopy, thermogravimetric analysis (DTG), and transmission electron microscopy (TEM). To reach a promising dispersibility in oil media, MWCNTs were functionalized with HA. While the cylindrical structures of MWCNTs were remained reasonably intact, characterization results consistently confirmed the sidewall-functionalization of MWCNTs with HA functionalities. Then, HA-treated MWCNTs-based turbine oil nanofluids (HA-MWCNTs/TO) with different volume fractions were synthesized and employed to be investigated in terms of heat transfer potential. Convective heat transfer coefficient of HA-MWCNTs/TO as a positive parameter and pressure drop as a negative factor were investigated for various volume fractions. While results suggested a weak increase in the pressure drop by MWCNTs loading into the TO, lack of acidic agents, the performance index higher than 1 and a significant increase in the convective heat transfer open a new gateway for introducing this economical product for industrial applications in turbines and can be a capable alternative for conventional TO.